Influence of growth temperature on titanium sulphide nanostructures: from trisulphide nanosheets and nanoribbons to disulphide nanodiscs. Issue 2 (2nd January 2019) - Talib, Mohammad; Tabassum, Rana; Islam, S. S.; Mishra, Prabhash
Abstract : We report the fabrication and characterization of titanium sulphide nanostructures using a chemical vapour transport (CVT) method. Abstract : We report the fabrication and characterization of titanium sulphide nanostructures using a chemical vapour transport (CVT) method. In CVT, reactions occur between titanium and sulphur powder in the vapor phase for TiS x nanostructure growth. Systematic studies on the effect of temperature, consequent structural evolution and optical properties were investigated by various characterization techniques. A series of experiments were performed by maintaining a fixed compositional ratio (1 : 3) of Ti and S within a temperature range from 400 °C to 650 °C. On increasing the temperature from 400 °C to 650 °C; a gradual change in morphology was obtained from nanosheets (NS) to mixed phase nanoribbons and nanosheets (NS: NR), nanoribbons (NR), and nanodiscs (ND) of titanium sulphide, which was confirmed using SEM/TEM analysis. Then, the composition of titanium sulphides was studied using XRD, EDX and Raman spectroscopic techniques and it is observed that NS, NR and NS: NR have the composition ratio of TiS3 whereas ND has a ratio of TiS2 . The phenomenon of decomposition of TiS3 into TiS2 at elevated temperatures was explained using thermogravimetric analysis (TGA) and differential thermal analysis (DTA) along with pictorial representations. The optical properties of the prepared TiS3 /TiS2 nanostructures were studied using UV-vis and photoluminescence spectroscopy. It is concluded that composition ratio of Ti and S as well as the temperature variation plays a crucial role in the formation of different Ti–S nanostructures with unique optical, electronic and thermal properties.